Utilization of Local Community Wisdom Through Nutraceutical Innovation of Japanese Papaya Leaf Cereal and Honey as a Preventive for Stunting and Immunomodulator in the Baduy Tribe - Agung Dewantoro; Nurwulan Adi Ismaya; Sunny Koswara Rahajeng (Jurnal Kefarmasian Indonesia, 2026)
Stunting remains a significant public health problem in Indonesia, especially in indigenous communities such as the Baduy tribe. Intervention through functional food innovations based on local natural ingredients are considered strategic. This study aims to develop nutraceutical cereal preparations from Japanese papaya leaves (Cnidoscolus aconitifolius) and honey as a stunting prevention and immunomodulator. This experimental study consisted of the formulation and evaluation stages of three cereal formulas (F1, F2, F3) containing varying concentrations of Japanese papaya leaves (10%, 15%, 20%) and honey. The evaluation included granule characteristics (organoleptic, particle size, compressibility index, water content, granule flow), cereal characteristics after reconstitution (pH, viscosity, sedimentation, microbiology), proximate tests, heavy metals, nutritional adequacy, and hedonic tests by Baduy children. The results of this study showed that Formula 2 showed the best physical characteristics with a compressibility index of 7% and optimal flow rate. Formula 1 excelled in protein content (21.57 g/100 g) and viscosity, while Formula 2 received the highest score in the hedonic test (most preferred response). All formulas met SNI and BPOM standards for microbiological safety and heavy metals. Formulas 1 and 2 met BPOM criteria as a food source of protein (≥10% RDA). The conclusion of this study is that the combination of Japanese papaya leaves and honey in the form of granular cereal is worthy of being developed as a functional food for stunting prevention and a natural immunomodulator for children, especially in traditional communities such as the Baduy tribe.